Mining and Energy Commodity Price Effects on Colombian Economy - Oviedo-Gómez, Andres; Candelo-Viafara, Juan Manuel (Cuadernos de Administración, 2020)
The Colombian economy has a strong dependence on the export of commodities. Different studies show that the prices of these products are exogenous, which have originated direct effects on the national economic activity. Therefore, this paper studies the shock effects produced by mining and energy commodity price variations like oil, coal and nickel on Colombian economy. We used 129 variables for 2001-2016 period and estimated a FAVAR model (Factor Augmented VAR) to observe commodity price effects on different economic aggregates, the results show that price fluctuations have significant effects on variables such as economic activity, investment, the trade balance, the real exchange rate and external debt.